Recurrent arthritis: an unusual diagnosis. (July 2020) - Sesama, Meenakshi; Bhaskar, Vikram; Meena, Monika; Narang, Manish; Aggarwal, Anju; Kotru, Mrinalini
Musculoskeletal complaints may be the initial manifestation of childhood leukaemias. When these symptoms predominate at the onset, a diagnosis of one of several rheumatic diseases may be entertained. Where blood tests are normal, no bone marrow examination would normally be indicated. The use of immune-suppressing medication, such as steroids, may lead to diagnostic delay or misdiagnosis.